“Evaluación del efecto residual de enmienda calcio magnesica en el rendimiento del frijol caupi (vigna unguiculata) en suelos acidos de aucaloma, como tercer cultivo evaluado” - Alegria Lozano, Víctor Segundo (2003)
The present work was driven in the experimental field of the 1 found Aucaloma of the U.N.S.M., county of you Lick Region San Martin (Peru), located geographically to 6° 29' South Latitude and 76° 21' Longitude West to an altitude of 650 msnm. The objective of the experiment was to evaluate the residual effect of 15 dose of the magnesic amendment calcium after of sixteen months of application in the floor, on the yield of the cultivation of bean caupí and to carry out the economic analysis of the best treatments. You uses the statistical design of block complete randomizado (BCR) with tour repetitions and 15 treatments. To check the studied variables, you uses the variance analysis and the test from Duncan to 0,05% of probability. The characteristics of the floor were of sandy texture franc, sour reaction (pH 5.76) content of organic matter (3,22%), with match readiness (12ppm), contained first floor of interchangeable ions and saturation of relatively high aluminum (67,5). The valued treatments were 0,0, 0,5, 1,0, 1,5, 2,0, 2,5, 3,0, 3,5, 4,0, 4.5, 5,0, 5,5, 6,0, 6,5 and TM/Ha of the magnesic amendment calcium (magnecal). Of the obtained results you concludes that significant difference existed far the dose of the applied magnesic amendment calcium, showing decrease in the grain yields with the increase of dose of the amendment, having stood out the T1 (0,0 TM/Há) and T2 (0,5 TM/Há) with the biggest grain yields with 1 227 and 1 198 Kg/Ha respectively. But with none of the treatments he/she obtained economic benefits, since the yields of grain of the frijol caupí responded very low to the residual effect in each one of the doses of the amendment whose relationship B/C obtained as maximum value 0,66. He/she was not significant difference far the parameter of plant height in none of the treatments. With regard to the chemical characteristics of the floor, highly significant difference existed as far the pH levels, Ca + Mg, Potassium and Aluminum except far the match that significant difference didn't exist among the treatments after the crop of the fríjol caupí. Also observing the analysis of the chemical characteristics of the floor of the first evaluation of the 15 doses of the magnesic amendment calcium, the pH levels, Ca + Mg, Potassium, Aluminum even in the match it existed highly significant differences. On the other hand, after the crop of the frijol caupí it is observed a decrease of the pH and diverse evaluated nutrients and for the opposite an increment of the agreement aluminum with the decrease of the dose of the magnesic amendment calcium and that to bigger dose of the amendment a bigger permanency of the nutrients exists in the floor and therefore a bigger residual effect. Gg